Target areas for harmonizing the Grain for Green Programme in China's Loess Plateau. (27th December 2019) - Geng, Qingling; Ren, Qingfu; Yan, Huimin; Li, Longhui; Zhao, Xining; Mu, Xingmin; Wu, Pute; Yu, Qiang
Abstract: Widespread land degradation has stimulated the implementation of a large‐scale ecological restoration programme in China's Loess Plateau—the Grain‐for‐Green Programme (GFGP). This programme has substantially increased vegetation cover and served to control soil erosion, but threatened regional food supply due to widespread cropland conversion. Consequently, a strategy balancing green and grain land uses is required. Here, we establish a dominance index of ecosystem services by quantifying the economic value of four key ecosystem services (net primary productivity, soil conservation, water yield, and food production), by combining spatially explicit datasets and census data. Using the dominance index, we identify the optimal areas to target for GFGP in the Loess Plateau. The identified areas (target areas) were the transition zone from low to high value of ecosystem services (ESV). These areas exhibited low grain productivity in addition to having the highest potential for soil conservation. Compared with other regions of the Loess Plateau, the loss of grain production due to cropland conversion in these target areas could decrease by 42%, whereas ESV could increase by 33%. Therefore, despite the fact that over the past 15 years (2000–2014) in these target areas more cropland was converted into ecological use (i.e. forest/grassland), there is still a need to strengthen ecological restoration in this region in the future. This study proposed a strategy for balancing green and grain from a spatial perspective, which could potentially solve land degradation issues and the tradeoff between ecosystem services in a more beneficial and targeted way.